Editorial - Adriana Benevides Soares; Ana Maria Lopes Calvo Feijoo; Ariane Patrícia Ewald; Deise Mancebo; Eleonôra Torres Prestrelo; Rita Maria Manso de Barros (Estudos e Pesquisas em Psicologia, 2010)
Adriana Benevides Soares, Ana Maria Lopes Calvo Feijoo, Ariane Patrícia Ewald, Deise Mancebo, Eleonôra Torres Prestrelo, Rita Maria Manso de Barros